Medicine students mental health situation around the world: a systematic review - Proença, Camille Schmidt de (2021)
The aim of this study was to survey the mental situation of medical students around the world. Systematic searches were carried out in the databases of journals, with terms related to the subject, preferentially choosing more recent works. It was noticed that medical students are more likely than other people to have problems related to mental health. The main problems reported in the reviewed studies were those related to anxiety, depression, stress and suicidal ideation. The percentages found were high and worrying, the problems according to the articles are largely caused by the situation imposed on university students, due to the deep and extensive contents necessary for the training of physicians, which ends up causing difficulties in learning and lack of time for pleasurable everyday activities. Towards the end of the course, contact with the suffering of sick people and situations of death have also been reported as factors that can contribute to the increase in the number of students with problems. Thus, it is of crucial importance that the universities' social assistance bodies monitor the situation closely, with a view to providing the necessary care to all students who need it, in time to remedy the situation, approaching and working the issue with academics, to reduce prejudice and increase acceptance and understanding of all this issue by undergraduates, encouraging them to identify the situation and seek help, whenever they perceive the need.